Enhanced amphiregulin exposure promotes modulation of the high grade serous ovarian cancer tumor immune microenvironment - Ebott, Jasmine; McAdams, Julia; Kim, Chloe; Jansen, Corrine; Woodman, Morgan; De La Cruz, Payton; Schrol, Christoph; Ribeiro, Jennifer; James, Nicole (Frontiers in Pharmacology, 2024)
High grade serous ovarian cancer (HGSOC) is a lethal gynecologic malignancy in which chemoresistant recurrence rates remain high. Furthermore, HGSOC patients have demonstrated overall low response rates to clinically available immunotherapies. Amphiregulin (AREG), a low affinity epidermal growth factor receptor ligand is known to be significantly upregulated in HGSOC patient tumors following neoadjuvant chemotherapy exposure. While much is known about AREG's role in oncogenesis and classical immunity, it's function in tumor immunology has been comparatively understudied. Therefore, the objective of this present study was to elucidate how increased AREG exposure impacts the ovarian tumor immune microenvironment (OTIME). Using NanoString IO 360 and protein analysis, it was revealed that treatment with recombinant AREG led to prominent upregulation of genes associated with ovarian pathogenesis and immune evasion (CXCL8, CXCL1, CXCL2) along with increased STAT3 activation in HGSOC cells. In vitro co-culture assays consisting of HGSOC cells and peripheral blood mononuclear cells (PBMCs) stimulated with recombinant AREG (rAREG) led to significantly enhanced tumor cell viability.Moreover, PBMCs stimulated with rAREG exhibited significantly lower levels of IFNy and IL-2. In vivo recombinant AREG treatment promoted significant reductions in circulating levels of IL-2 and IL-5. Intratumoral analysis of recombinant AREG treated mice revealed a significant reduction in CD8+ T cells coupled with an upregulation of PD-L1. Finally, combinatorial treatment with an AREG neutralizing antibody and carboplatin led to a synergistic reduction of cell viability in HGSOC cell lines OVCAR8 and PEA2. Overall, this study demonstrates AREG's ability to modulate cytotoxic responses within the OTIME and highlights its role as a novel HGSOC immune target.